Scooby-Doo! World of Mystery 35 Ecuador - Galapagos Island - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang arrive on the faraway Galapagos Islands and meet a shaggy creature that is not all it seems...
Keywords: Juvenile literature-Fiction